2020
DOI: 10.1001/jamanetworkopen.2020.3833
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Frequency of Sexual Activity and Number of Sexual Partners Among Adults Aged 18 to 44 Years in the US, 2000-2018

Abstract: IMPORTANCE Sexual relationships are important for well-being and health. Recent trends in sexual activity among US adults are unknown. OBJECTIVES To examine trends in reported frequency of sexual activity and number of sexual partners by sex and age and the association between measures of sexual activity and sociodemographic variables. DESIGN, SETTING, AND PARTICIPANTS In this survey study, repeat, cross-sectional analyses of participants aged 18 to 44 years from 10 rounds of the General Social Survey (2000-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 46 publications
(93 reference statements)
8
77
4
Order By: Relevance
“…Over the past several decades, the frequency with which adults engage in sexual intercourse has declined in the United States (Twenge et al, 2017a) and some other developed countries (e.g., Beutel et al, 2018). In the United States., the decline in sexual activity has been particularly acute among teenagers and young adults (Abma & Martinez, 2017; Ethier et al, 2018; Twenge et al, 2017b; Ueda et al, 2020). The sources of this decline have received little empirical attention, as explanations have fallen largely in the realm of scholarly conjecture (e.g., Wilcox & Sturgeon, 2018) or journalistic speculation (e.g., DePaulo, 2018; Ingraham, 2019; Julian, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, the frequency with which adults engage in sexual intercourse has declined in the United States (Twenge et al, 2017a) and some other developed countries (e.g., Beutel et al, 2018). In the United States., the decline in sexual activity has been particularly acute among teenagers and young adults (Abma & Martinez, 2017; Ethier et al, 2018; Twenge et al, 2017b; Ueda et al, 2020). The sources of this decline have received little empirical attention, as explanations have fallen largely in the realm of scholarly conjecture (e.g., Wilcox & Sturgeon, 2018) or journalistic speculation (e.g., DePaulo, 2018; Ingraham, 2019; Julian, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Measures of health status included whether respondents were a current consumer of alcohol (“Do you drink alcohol?”), and a smoker (“Do you smoke?”), and possible answers for these two questions comprised “yes”, or “no”; “Have you ever been diagnosed by a health professional with: (tick all that apply)”: “hypertension”, “obesity”, “myocardial infarction”, “angina pectoris and other coronary diseases”, “other cardiac diseases”, “varicose veins of lower extremities”, “osteoarthritis”, “chronic neck pain”, “chronic low back pain”, “chronic allergy (excluding allergic asthma)”, “asthma (including allergic asthma)”, “chronic bronchitis”, “emphysema or chronic obstructive pulmonary disease (COPD)”, “type 1 diabetes”, “type 2 diabetes”, “diabetic retinopathy”, “peptic ulcer disease”, “cataract”, “urinary incontinence or urine control problems”, “hypercholesterolemia”, “chronic skin disease”, “chronic constipation”, “liver cirrhosis and other hepatic disorders”, “stroke”, “chronic migraine and other frequent chronic headaches”, “hemorrhoids”, “cancer”, “osteoporosis”, “thyroid disease”, “injury”, and “renal disease”. Psychiatric conditions included both anxiety and depression estimated through the Spanish version of Beck inventories of depression and anxiety [ 12 , 13 ] as well as the option to declare “other psychiatric conditions”. Moreover, participants were asked if they had experienced any physical symptoms of COVID-19 during the confinement: “What guidelines are you following for self-isolation?”, and responses comprised the selection of one or more of the following symptoms: “high temperature”, “persistent cough”, “sore throat”, and “runny nose”.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the benefits of regular sexual activity also extend to populations of younger adults; a recent study by Carcedo et al [ 10 ] observed higher levels of sexual satisfaction to be associated with lower levels of depression among Spanish young adults, which in turn has been observed to be mediated by the frequency of sexual activity [ 11 ]. Despite this knowledge, trends in the frequency of sexual inactivity among adults aged 18 to 44 years have importantly increased over recent decades in countries such as the United States [ 12 ]. Similarly, a declining trend regarding the frequency of sexual activity has been recently identified in Britain, particularly more accentuated among those in early middle age and those who were married or cohabiting [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leisure sex approach also helps understand the trend of young people having less sex in comparison with previous generations, particularly among young men (Ueda et al, 2020). Evidence suggests this is attributable to the increased availability of pornography and the declining stigmatization of masturbation, meaning sexual satisfaction can be gained outside the traditional model of monogamous, dyadic sexual intercourse (Anderson, 2012), rather than this decrease being the result of more restrictive sexual norms.…”
Section: Literature Review: Normalization and Liberalizationmentioning
confidence: 99%